Experimental study on fracture characteristics of rock-like material with prefabricated cracks under compression shear - Shuang-Xi Yuan; Tong Jiang; Jia-Hua Lei; Cheng-Hao Cui (Scientific Reports, 2022)
Abstract In order to understand the effects of different patterns of prefabricated fractures and grain size compositions on the fracture characteristics, acoustic emission characteristics and mechanical properties of the rock masses. We conducted compression shear experiments on square rock masses with different modes of prefabricated fractures and different grain size compositions. The experimental results showed that five fracture patterns were produced in specimens with different fracture patterns. The first fracture specimen, the fourth fracture specimen and the fifth fracture specimen were all brittle fractures. The other four specimens were not brittle fractures. The fracture patterns, fracture processes and mechanical characteristics of the different fracture pattern rock masses were revealed. The lowest peak shear stresses were found in specimens consisting of two grain size ranges and the highest peak shear stresses were found in specimens consisting of three grain size ranges. The highest shear displacements corresponding to the peak shear stresses were found in the specimens consisting of three particle size ranges. The effect of different grain size compositions on the peak shear stress and its corresponding shear displacement of the rock mass was revealed. Specimens consisting of one grain size range produced significant fracture and acoustic emission prior to the peak shear stress. The acoustic emission was jumped after the main fracture was formed. The specimen consisting of two grain size ranges produced fractures and strong acoustic emission characteristics after the peak shear stress. Thereafter, fracture reappeared and the acoustic emission signature increased again. As the specimen entered the residual strength phase, the acoustic emission was jumpy. Specimens consisting of three grain size ranges were brittle fractures with weak acoustic emission characteristics after the main fracture has formed. The cumulative energy of shear acoustic emission was the highest for a rock mass consisting of three grain size ranges. The rock mass consisting of three grain size ranges was also the strongest and most difficult to fracture because the grains were more fully embedded in each other.